If AB = I, then BA = I.

If AB = I,
then AB has full rank.
then B also has full rank.
If AB = I
BAB = BI
BAB = B
BAB = IB
BAB – IB = 0
(BA-I)B = 0
This can only happen if BA-I=0, as B has full rank.
hence BA = I.

Advertisements
This entry was posted in Uncategorized. Bookmark the permalink.

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s